Application Timing Efficacy of Enlist Duo in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2019)
In this study, herbicides were tested to compare application timing for weed control in irrigated corn. All herbicides tested provided season-long control (90% or more) of Palmer amaranth, Russian thistle, quinoa, and common sunflower. The inclusion of Enlist Duo to SureStart II as an early postemergence (V2) treatment increased kochia and johnsongrass control compared to a preemergence treatment of SureStart II alone early in the season. However, by later in the year, control of kochia and johnsongrass was best when Enlist Duo application was delayed until the V4 stage. Enlist Duo provided equal control of all weeds when applied at 3.5 or 4.67 pt/a, and corn yields did not differ between Enlist Duo rates within application timings. Corn treated at the V2 stage yielded 210–216% more grain than untreated corn, whereas corn receiving Enlist Duo at the V4 stage yielded 257–263% more grain than the weedy controls.
Keywords: herbicide resistance